VARIASI KONSENTRASI JELLY POWDER PADA PEMBUATAN JELLY DRINK BROKOLI (Brassica oleracea var. Italica) - Widjaja, Willy Pranata; Cahyadi, Wisnu; Suliasih, Neneng; Ridzkiani, Hana Putri (Pasundan Food Technology Journal (PFTJ), 2025)
This study investigates the effect of jelly powder concentration on the quality characteristics of broccoli jelly drink (Brassica oleracea var. Italica). A randomized block design with four levels of jelly powder (0.6%, 0.7%, 0.8%, and 0.9%) was applied. Parameters analyzed included pH, vitamin C content, viscosity, sensory attributes (color, aroma, taste, suction power), and antioxidant activity (IC₅₀) for the best treatment. Results showed significant effects (p < 0.05) of jelly powder concentration on all variables. Higher concentrations increased viscosity but decreased pH, vitamin C stability, and sensory acceptability. The 0.6% concentration was selected as optimal, showing balanced pH (4.78), viscosity (198.83 cP), vitamin C (131.67 mg/100 g), and favorable sensory scores. However, its antioxidant activity was classified as very weak (IC₅₀ = 4667.89 ppm). Optimization is required to enhance functional benefits.